TRANSFORMING PEDAGOGY: SHIFTING PERSPECTIVE FROM TEACHER-CENTRED TO STUDENT-CENTRED AT SECONDARY LEVEL EDUCATION IN PAKISTAN - Anjum, Rahila (My University, 2025)
This study investigates the extent to which student-oriented methods are executed by the secondary level teachers and also explores the challenges teachers encounter in implementing these approaches. Student-centered methods are based on constructivism theory which aims to change the outdated role of instructor from lecturer to facilitator. In spite of all advantages, the execution of this cooperative learning is still uneven across educational environments. By utilizing mixed-method approach, the study gathered data through planned questionnaire including open-ended answers from teachers teaching at secondary level. Hierarchical cluster analysis and thematic analysis were used to recognize patterns in educators’ attitudes and challenges. The results show that although teachers favor the cooperative learning, yet their actual employment of this approach is limited or shallow, challenged by issues including excessive workload, unsupportive administration, lack of teachers training and limited use of technology. The research also explores four different images of the future grounded on teacher perceptions and execution patterns: The pedagogical trendsetters, Balanced Innovators, Hesitant Implementers and Traditionalists Holding Ground. These images focused the level of implementation across various teaching contexts and present insight into the psychological and physical aspects affecting teachers’ attitudes. The research contributes to the increased number of literatures through presenting a real perception of how cooperative learning is recognized and implemented at the secondary level teaching. It presents insights for teachers, management and officials to plan focused strategies to guide towards a steady and sustainable shift from teacher-centered to student-centered approach.

یہ مطالعہ اس بات کی چھان بین کرتا ہے کہ ثانوی سطح کے اساتذہ کے ذریعہ طالب علم پر مبنی طریقوں کو کس حد تک نافذ کیا جاتا ہے اور ان چیلنجوں کا بھی پتہ چلتا ہے جو اساتذہ کو ان طریقوں کو نافذ کرنے میں درپیش ہیں۔ طلباء پر مبنی طریقے تعمیری نظریہ پر مبنی ہیں جس کا مقصد استاد کے فرسودہ کردار کو لیکچرر سے سہولت کار میں تبدیل کرنا ہے۔ تمام فوائد کے باوجود، اس کوآپریٹو لرننگ کا نفاذ تعلیمی ماحول میں اب بھی ناہموار ہے۔ مخلوط طریقہ کار کو استعمال کرتے ہوئے، مطالعہ نے منصوبہ بند سوالنامے کے ذریعے ڈیٹا اکٹھا کیا جس میں ثانوی سطح پر پڑھانے والے اساتذہ کے کھلے عام جوابات شامل ہیں۔ درجہ بندی کے کلسٹر تجزیہ اور موضوعاتی تجزیہ کا استعمال اساتذہ کے رویوں اور چیلنجوں کے نمونوں کو پہچاننے کے لیے کیا گیا تھا۔ نتائج ظاہر کرتے ہیں کہ اگرچہ اساتذہ کوآپریٹو لرننگ کے حق میں ہیں، پھر بھی اس نقطہ نظر کے لیے ان کا حقیقی روزگار محدود یا کم ہے، جس میں کام کا زیادہ بوجھ، غیر معاون انتظامیہ، اساتذہ کی تربیت کی کمی اور ٹیکنالوجی کا محدود استعمال شامل ہیں۔ اس تحقیق میں مستقبل کی چار مختلف تصاویر بھی دریافت کی گئی ہیں جو اساتذہ کے تصورات اور عمل درآمد کے نمونوں پر مبنی ہیں: تدریسی رجحان ساز، متوازن اختراع کرنے والے، ہچکچاہٹ پر عمل کرنے والے اور روایت پرست ہولڈنگ گراؤنڈ۔ یہ تصاویر مختلف تدریسی سیاق و سباق میں عمل درآمد کی سطح پر مرکوز تھیں اور اساتذہ کے رویوں کو متاثر کرنے والے نفسیاتی اور جسمانی پہلوؤں کی بصیرت پیش کرتی ہیں۔ یہ تحقیق ثانوی سطح کی تدریس میں کوآپریٹو لرننگ کو کس طرح تسلیم اور لاگو کیا جاتا ہے اس کا حقیقی تاثر پیش کرنے کے ذریعے ادب کی بڑھتی ہوئی تعداد میں معاون ہے۔ یہ اساتذہ، انتظامیہ اور حکام کے لیے بصیرت پیش کرتا ہے کہ وہ استاد کے مرکز سے طالب علم پر مبنی نقطہ نظر کی طرف ایک مستحکم اور پائیدار تبدیلی کی طرف رہنمائی کے لیے مرکوز حکمت عملیوں کی منصوبہ بندی کریں۔